Ecosystem Changes Following Restoration of a Buckthorn‐Invaded Woodland. Issue 1 (11th April 2013) - Larkin, Daniel J.; Steffen, James F.; Gentile, Rachel M.; Zirbel, Chad R.
Abstract Shifts in plant‐community composition following habitat degradation and species invasions can alter ecosystem structure and performance of ecosystem services. In temperate North American woodlands, invasion by aggressive Eurasian shrubs has produced dense thickets with depauperate understory vegetation and increased rates of litter decomposition and nutrient cycling, attributes that could impair storage of carbon as soil organic matter (SOM). It is important to know if such impairment has occurred and, if so, the extent to which restoration can return this service. We used an oak‐woodland restoration chronosequence in northeastern Illinois to contrast structural and functional attributes of unrestored areas dominated by Rhamnus cathartica (common buckthorn) with areas that had undergone buckthorn removal and ongoing, active management for less than 1 to 14 years. With increasing age, restored areas had higher understory plant diversity and cover (p < 0.0001 and 0.005, respectively) and higher litter mass (p = 0.018). These structural differences were associated with some evidence of reduced soil erosion (p = 0.027–0.135) but greater soil CO2 efflux (p = 0.020–0.033). Total particulate organic matter (POM) in the soil increased with restoration age, which was driven by increases in the slow‐turnover, mineral‐associated SOM fraction. However, variance was high and relationships were only weakly significant (p = 0.082 and 0.083 for total POM and mineral‐associated SOM, respectively). Our results suggest that, in addition to better documented biodiversity benefits, beneficial changes to ecosystem properties and processes may also occur with active, long‐term restoration of degraded woodlands.